AI-driven agribusiness sustainability: Optimizing supply chains for reduced environmental impact - Amayreh Khalid Thaher (E3S Web of Conferences)
The article is devoted to the study of the role of artificial intelligence (AI) in increasing the efficiency of supply chains in agribusiness, which is a topical topic in the context of global challenges and growing requirements for the sustainability of agricultural production. With the development of technologies and the increase in data volumes, the use of AI allows to significantly increase the accuracy of forecasting, improve inventory management, logistics and product quality, which makes the introduction of these technologies in agribusiness necessary. The purpose of the work is to analyze the influence of AI on the optimization of supply chains in agribusiness, to identify the main directions of its application and to estimate potential benefits for the industry. The tasks of the study include the analysis of existing AI implementation methods, the assessment of its influence on the process of logistics and inventory management in agribusiness. Research methods include an analytical literature review, statistical data analysis, and structuring of examples of real implemented AI in the agricultural sector. The main results and recommendations of the research will allow to increase the efficiency of supply chains, reduce costs, improve quality and increase the sustainability of business in the conditions of uncertainty.